Genetic diversity of the Nubian ibex in Oman as revealed by mitochondrial DNA. Issue 5 (26th May 2021) - Al-Ghafri, Mataab K.; White, Patrick J. C.; Briers, Robert A.; Dicks, Kara L.; Ball, Alex; Ghazali, Muhammad; Ross, Steven; Al-Said, Taimur; Al-Amri, Haitham; Al-Umairi, Mudhafar; Al-Saadi, Hani; Aka'ak, Ali; et al.
Abstract : The Nubian ibex ( Capra nubiana ) is patchily distributed across parts of Africa and Arabia. In Oman, it is one of the few free-ranging wild mammals found in the central and southern regions. Its population is declining due to habitat degradation, human expansion, poaching and fragmentation. Here, we investigated the population's genetic diversity using mitochondrial DNA (D-loop 186 bp and cytochrome b 487 bp). We found that the Nubian ibex in the southern region of Oman was more diverse (D-loop HD; 0.838) compared with the central region (0.511) and gene flow between them was restricted. We compared the genetic profiles of wild Nubian ibex from Oman with captive ibex. A Bayesian phylogenetic tree showed that wild Nubian ibex form a distinct clade independent from captive animals. This divergence was supported by high mean distances (D-loop 0.126, cytochrome b 0.0528) and high F ST statistics (D-loop 0.725, cytochrome b 0.968). These results indicate that captive ibex are highly unlikely to have originated from the wild population in Oman and the considerable divergence suggests that the wild population in Oman should be treated as a distinct taxonomic unit. Further nuclear genetic work will be required to fully elucidate the degree of global taxonomic divergence of Nubian ibex populations.